Investigasi Interleaved Boost Converter menggunakan kontroler Linear Quadratic Regulator (LQR) - Safitra, Ade; Wiryajati, I Ketut; Nrartha, I Made Ari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The Boost DC-DC Converter plays a significant role in renewable energy applications and electric vehicles, serving to increase the output voltage from low-voltage sources. This study aims to analyze the performance of the Interleaved Boost Converter with Linear Quadratic Regulator (LQR) control compared to open loop and PID control. The research methodology involves designing and simulating the converter using MATLAB/Simulink, where various control configurations are tested to assess their ability to regulate output voltage. Simulation results show that the Interleaved Boost Converter with LQR control produces a stable output voltage of 28 volts with the fastest response time (9.629 µs) and no overshoot. In contrast, the PID control configuration delivers an output voltage of 28.46 volts with a maximum overshoot of 0.510% and a slower response time (25.177 µs). The open loop configuration, despite having the fastest response time (19.768 µs), results in significant voltage ripple. The conclusion of this study emphasizes that LQR control is superior in terms of stability and quick response and is recommended for applications requiring high performance. Future research is suggested to focus on optimizing PID control parameters and evaluating LQR performance under dynamic load conditions